Quality of Life and Attractiveness of Small Towns: A Comparison of France and Poland - Kwiatek-Sołtys, Agnieszka; Mainet, Helene (Quaestiones Geographicae, 2014)
Nowadays the issue of the quality of life tends to be more and more important for the attractiveness of spaces in the context of increasing commuting and social demand for a good living environment. Small towns are often seen as places where “the living is easy” and social ties are dense. They are therefore a good basis for analysing the quality of life. This is a transversal and complex notion which is not always easy to define. This paper is based on surveys conducted in small Polish and French towns in order to analyse perceptions of the quality of life by both their inhabitants and local leaders, and their potential place in the attractiveness of small towns.